If you aim higher than you expect, you could reach higher than you dream: Leadership and employee performance - Naveed Ahmad Khan; Silke Michalk; Kirill Sarachuk; Hafiz Ali Javed (Economies, 2022)
Leadership is about lifting a person's vision, raising their productivity to higher standards and creating a personality beyond their usual capabilities. Our study examines the Pygmalion effect and leader-member exchange (LMX) on employee task performance via organizational commitment. The data was collected from 280 middle-level managers from top ten banks in Pakistan. This study offers three main contributions to the literature. First, our results discover a strong link between the Pygmalion effect, LMX and employees' task performance through mediation of organizational commitment. Secondly, our study indicates that leaders should have higher quality relationships with employees and higher task performance expectations. Finally, most previous studies focused on leadership approaches or have been conducted in western developed countries. To our knowledge, this study is a unique contribution to the literature on leaders' expectations in changing and diverse environments, as in underdeveloped countries like Pakistan.
Keywords: 330; commitment; employee performance; leader-member exchange (LMX); leaders expectations; social exchange